Stakeholders Collaboration in Optimizing Tourism and Creative Economy Integration - Khusaini, Moh.; Finuliyah, Firdaus; Lestari, Alfi Muflikhah; Yulianti, Nida (Journal of Indonesian Tourism, Hospitality and Recreation, 2024)
ABSTRACTTourism development has a very important role in driving the economic growth of a country. Tourism contributes to national income, through job creation, foreign exchange earnings, market creation for native commodities, and promotion of local products. Tourism development has great potential as a multiplier effect in the development of the creative economy. Pentahelix, as the main stakeholder, plays a key role in the socio-economic progress of the region, including encouraging the development of tourism and the creative economy. This study aims to determine the influence of the role of stakeholders on the development of tourism and the creative economy in Pasuruan Regency using the PLS method. The results of the study showed that only academics had a significant influence on efforts to increase the attractiveness of tourist villages. Meanwhile, on the creative economy side, only the role of the government has had a positive impact on increasing digitalization. Based on the results of these estimates, it is important for Pasuruan Regency to develop the concept of integrating tourism and the creative economy or community-based creative tourism.ABSTRAKPembangunan pariwisata memiliki peran yang sangat penting dalam mendorong pertumbuhan ekonomi suatu negara. Pariwisata berkontribusi dalam memberikan sumbangan terhadap pendapatan nasional, melalui penciptaan lapangan kerja, penerimaan devisa, penciptaan pasar untuk komoditas asli, dan promosi produk-produk lokal. Pengembangan pariwisata memiliki potensi besar sebagai multiplier effect dalam pengembangan ekonomi kreatif. Pentahelix, sebagai pemangku kepentingan utama memainkan peran kunci dalam kemajuan sosial-ekonomi daerah, termasuk mendorong pembangunan pariwisata dan ekonomi kreatif. Penelitian ini bertujuan untuk mengetahui pengaruh peran stakeholders terhadap pengembangan pariwisata dan ekonomi kreatif di Kabupaten Pasuruan dengan menggunakan metode PLS. Hasil penelitian menunjukkan, hanya akademisi yang berpengaruh signifikan terhadap upaya peningkatan daya tarik desa wisata. Sedangkan, pada sisi ekonomi kreatif hanya peran pemerintah yang telah berdampak positif terhadap peningkatan digitalisasi. Berdasarkan hasil estimasi tersebut maka Kabupaten Pasuruan penting untuk mengembangkan konsep integrasi pariwisata dan ekonomi kreatif atau community-based creative tourism.